North Korea after the 1990s: The (un)Developmental State? - Anantasirikiat, Seksan (Journal of Social Sciences Naresuan University, 2025)
North Korea has been in a stagnation since the 1990s. To explain this phenomenon, various scholarships apply mixed methods, including historical approach (cause-effect linkages), external conditions especially North Korea and foreign relations with its neighboring countries, and comparative analysis with other successful socialist countries. This article examines North Korea’s development post 1990s through the lens of Nem Singh & Ovadia’s “developmental state” (2018) The core argument is North Korea after the 1990s is a failed developmental state. Although North Korea has continuity and positive factors for economic development from sources of growth, industrial policy especially flagship defense industry, poverty reduction record, and political base of development, there are some limitations in state capacity that the leader and state apparatus could not create better conditions for economic development, and external environment that North Korea encounters from the sanctions by the United Nations and United States of America.